C-reactive protein in the diagnosis of community-acquired pneumonia - Requejo,Henry I. Z. (2003)
Qualitative determination of C-reactive protein (CRP) was evaluated as a diagnostic method for community-acquired pneumonia. Paired serum and pleural fluid samples from child patients were examined with a CRP test, compared to bacterial cultures, counterimmunoelectrophoresis and immunoassay. The CRP test gave excellent parameters of sensitivity, specificity and predictive values for the diagnosis of bacterial pneumonia.